Proteasomal Degradation Machinery: Favorite Target of HIV-1 Proteins - Lata, Sneh; Mishra, Ritu; Banerjea, Akhil C. (Frontiers in Microbiology, 2018)
Proteasomal degradation pathways play a central role in regulating a variety of protein functions by controlling not only their turnover but also the physiological behavior of the cell. This makes it an attractive target for the pathogens, especially viruses which rely on the host cellular machinery for their propagation and pathogenesis. Viruses have evolutionarily developed various strategies to manipulate the host proteasomal machinery thereby creating a cellular environment favorable for their own survival and replication. Human immunodeficiency virus-1 (HIV-1) is one of the most dreadful viruses which has rapidly spread throughout the world and caused high mortality due to its high evolution rate. Here, we review the various mechanisms adopted by HIV-1 to exploit the cellular proteasomal machinery in order to escape the host restriction factors and components of host immune system for supporting its own multiplication, and successfully created an infection.